SALIENT FEATURES AND BIBLIOGRAPHY OF BIHAR HAIRY CATERPILLAR, SPILOSOMA OBLIQUA WLK. (LEPIDOPTERA : ARCTIIDAE) - GOEL, S.C.; KUMAR, SANJAY; BHARDWAJ, D.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
An attempt has been made on the salient features of Bihar hairy caterpillar, Spilosoma obliqua Wilk, a serious pest of agricultural importance; incorporating important aspects like distribution, biology, morphology, artificial diet, bioenergetics, insect pest and host specificity, various systems and pest management strategies. The scattered information available in literature on the pest were also compiled and presented in the form of a bibliography.